The ghostfaces eaudiobook - Flanagan, John (Brotherband Chronicles, 2016)
From John Flanagan, author of the worldwide bestselling Ranger's Apprentice, comes a brand-new chapter in the adventures of young Skandians who form a different kind of family—a brotherband. When the Brotherband crew are caught in a massive storm at sea, they’re blown far off course and wash up on the shores of a land so far west that Hal can’t recognize it from any of his maps. Eerily, the locals are nowhere in sight, yet the Herons have a creeping feeling they are being watched.   Suddenly the silence is broken when a massive, marauding bear appears, advancing on two children. The crew springs into action and rescues the children from the bear’s clutches, which earns them the gratitude and friendship of the local Mawagansett tribe, who finally reveal themselves. But the peace is short-lived. The Ghostfaces, a ruthless, warlike tribe who shave their heads and paint their faces white, are on the warpath once more. It’s been ten years since they raided the Mawagansett village, but they’re coming back to pillage and reap destruction. As the enemy approaches, the Herons gear up to help their new friends repel an invasion.   In this sixth book in the action-packed Brotherband Chronicles, the Herons find themselves in unfamiliar lands and prepare for battle with a ruthless, unknown enemy.